Breaking Malus' law: Highly efficient, broadband, and angular robust asymmetric light transmitting metasurface. Issue 5 (11th August 2016) - Zhang, Cheng; Pfeiffer, Carl; Jang, Taehee; Ray, Vishva; Junda, Maxwell; Uprety, Prakash; Podraza, Nikolas; Grbic, Anthony; Guo, L. Jay
Abstract : A few‐layer, asymmetric light transmitting metasurface consisting of coupled metallic sheets is reported. It has a measured transmission efficiency of 80%, extinction ratio of 13.8 dB around 1.5 μm, and a full width half maximum bandwidth of 1.7 μm. It is as thin as 290 nm, has good performance tolerance against the angle of incidence and constituent nano‐structure geometry variations. Abstract: High efficiency, broad bandwidth, and robust angular tolerance are key considerations in photonic device design. Here, a few‐layer, asymmetric light transmitting metasurface that simultaneously satisfies all the above requirements is reported. The metasurface consists of coupled metallic sheets. It has a measured transmission efficiency of 80%, extinction ratio of 13.8 dB around 1.5 μm, and a full width half maximum bandwidth of 1.7 μm. It is as thin as 290 nm, has good performance tolerance against the angle of incidence and constituent nano‐structure geometry variations. This work demonstrates a practical asymmetric light transmission device with optimal performance for large scale manufacturing.